1996
DOI: 10.1111/j.1525-1470.1996.tb00703.x
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study of Childhood Alopecia Areata in Chandigarh, India

Abstract: All new cases of alopecia areata (AA) were studied during the years 1983-1993. Eight hundred forty-one cases were recorded, including 201 (23.9%) children less than 16 years of age. The female:male ratio was 1.4:1 (117 girls, 84 boys) for childhood AA. Alopecia was severe, that is, total, universal, or extensive, in 34 (16.9%) children. Onset occurred in 77 (38.3%) children between ages 6 and 10 years, in 67 (33.3%) before 5 years of age, and in 57 (28.4%) between 11 and 16 years. Onset before 5 years of age w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
94
10
13

Year Published

2001
2001
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(137 citation statements)
references
References 20 publications
20
94
10
13
Order By: Relevance
“…Reported familial incidence in western literature varied from 20% to 40%. 8,15,18 Indian studies have reported an incidence of 1.7% and 8.7% respectively. 4,15 A study of AA in Singapore have reported an incidence of 4.6%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reported familial incidence in western literature varied from 20% to 40%. 8,15,18 Indian studies have reported an incidence of 1.7% and 8.7% respectively. 4,15 A study of AA in Singapore have reported an incidence of 4.6%.…”
Section: Discussionmentioning
confidence: 99%
“…8,15,18 Indian studies have reported an incidence of 1.7% and 8.7% respectively. 4,15 A study of AA in Singapore have reported an incidence of 4.6%. 5 Associated vitiligo was noted in 5% subjects suggesting an association between AA and vitiligo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hastalığın neden olduğu sosyal ve psikolojik etki nedeni ile aileler sıklıkla tıbbi destek ve tedavi için doktora başvurmaktadırlar 5,6,9 . Erişkin çağda görülen AA epidemiyolojisi daha iyi bilinirken çocukluk çağında AA ve eşlik eden komorbiditeleri ile ilgili ise yeterli çalışma bulunmamaktadır [4][5][6][7][8][9][10] . Bu çalışmada Türk çocuk popülasyonunda AA'ya eşlik eden komorbiditeler ve bu hastalıklar ile ilgili bazı epidemiyolojik ve laboratuvar değişkenlerin araştırılması amaçlanmıştır.…”
Section: Discussionunclassified
“…AA özellikle genç hastalarda görülür, hastaların yaklaşık %60'ı ilk ataklarını 20 yaş öncesinde geçirirler 1,2 . AA'ya vitiligo, otoimmün tiroidit, sistemik lupus eritematozus (SLE), diyabetes mellitus (DM) ve pernisiyöz anemi gibi başka otoimmün hastalıklar da eşlik edebilmektedir 3,4 . AA epidemiyolojisi erişkin çağda iyi bilinmesine rağmen, çocukluk çağında görülen AA ile ilgili bilgiler daha kısıtlıdır [4][5][6][7][8][9][10] .…”
Section: Introductionunclassified